Measuring the therapeutic relationship in Acceptance and Commitment Therapy - Ferreira, Ana Claudia Rodrigues; Silveira, Jocelaine M. (Perspectivas em Análise do Comportamento, 2025)
The intrapersonal aspects of Acceptance and Commitment Therapy (ACT) are frequently highlighted in the literature. However, it is known that non-specific, interpersonal factors also influence treatment outcomes. The present study aims to illustrate, using a therapeutic relationship measurement instrument developed in Portuguese and widely used in Brazil, how interpersonal aspects can influence an ACT treatment. The method employed was a case study, in which two elderly women (72 and 68 years old) participated. Their complaint consisted of discouragement and decreased engagement in pleasurable activities for more than a year. They were recruited and selected in the context of research on structured activities in ACT, focusing on values. For that, 16 sessions were held. The first and 16th consisted of assessment interviews. The instruments used were: Geriatrics Depression Scale (GDS) to characterize and to check exclusion criteria; Adapted and validated version for Brazil of the Acceptance and Action Questionnaire-II (AAQ-II), Version of the Life Values Questionnaire (VLQ), both for characterization and finally, the Multidimensional System for the Categorization of Behavior in Therapeutic Interaction (SiMCCIT), to which subcategories developed for the present study were added. Results: Correlations between therapist’s verbalizations in the interaction with one of the participants, taking them as indicative of important processes of psychological flexibility. The SiMCCIT codes of the other participant were disregarded for analysis, since the Kappa index was low. The scores of the other instruments were analyzed for both participants in order to characterize them at the beginning and at the end of the intervention. It is discussed how the interpersonal aspects of ACT can help elucidate outcome measures and shed light on processes to be considered by Process-Based Therapy (PBT). Among the limitations of the study, the impossibility of determining the effect of the 16 sessions applied to each participant stands out, since there is no stability or withdraw in the conditions. The low kappa index also constitutes a limitation for the analyses. The lack of external validity is another important limitation. On the other hand, the exploratory nature of the report on the care provided to the elderly women, relating process and outcome measures, has a heuristic value.